Видовой состав и зоогеографические особенности мизид (Crustacea, Mysida, Mysidae) Утлюкского и Молочного лимана (Северное Приазовье) - Васильковская, О.Б. (Вестник зоологии, 2012)
Приведены результаты многолетних исследований (1992–2010 гг.) по фауне, распространению и экологии мизид в различных участках Утлюкского и Молочного лиманов. Впервые в северо-западной части Азовского моря отмечены четыре вида мизид: Diamysis pengoi (Czerniavsky, 1882), Paramysis ullskyi (Czerniavsky, 1882), P. lacustris (Czerniavsky, 1882), P. intermedia (Czerniavsky, 1882). В этих лиманах семейство Mysidae представлено 14 видами и подвидами из 7 родов. В Утлюкском лимане отмечено 14, в Молочном — 11 видов. На основе анализа их экологического предпочтения установлено, что мизиды исследуемого региона имеют выраженный морской характер. По зоогеографическому составу они относятся к 5 комплексам. Обсуждается сходство структуры фаун мизид Утлюкского и Молочного лиманов. Дан сравнительный анализ динамики развития фауны мизид за последние двадцать лет. Results of studies of faunas, distribution and ecology of the mysid shrimps (Mysidae) in 1992—2010 in different areas of Utluk and Molochny Lagoons are provided. Four species of mysids, Diamysis pengoi (Czerniavsky, 1882), Paramysis ullskyi (Czerniavsky, 1882), P. lacustris (Czerniavsky, 1882), P. intermedia (Czerniavsky, 1882) are recorded for the first time from the north-western part of Molochny Lagoon. The family Mysidae is represented by 14 species and subspecies of 7 genera, of them, by 14 species in Utluk Lagoon, and 11 species in Molochny Lagoon. Based on the analysis of their ecological preserences , the mysids of this region are considered to be marine. The mysids in this area are shown to belong in 5 zoogegraphic complexes, depending on their preferences of water salinity. Similarities in the structure of Utluk and Molochny Lagoon faunas are discussed. Comparative analysis of the faunas dynamics in the last 20 years is given.